2010
DOI: 10.1158/1055-9965.epi-10-0008
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Cruciferous Vegetables Modifies Bladder Cancer Survival

Abstract: Background: Intake of cruciferous vegetables, a rich source of dietary isothiocyanates, has been inversely associated with risk of bladder cancer. Due to the potent antiproliferative effects of dietary isothiocyanates on bladder cancer in in vitro and in vivo models, cruciferous vegetable intake may also play a role in survival among patients with bladder cancer.Methods: Using information obtained from the Roswell Park Cancer Institute Tumor Registry, patient medical records, and routinely collected questionna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 22 publications
2
81
0
1
Order By: Relevance
“…In the organizations' combined documentFood, Nutrition, Physical Activity and the Prevention of Cancer: A Global Perspective Expert Report-, the main recommendations call for consuming a greater variety of vegetables, fruits, whole grains, and legumes; aiming for meals that consist of two thirds (or more) vegetables, fruits, whole grains, or beans and one third (or less) animal protein; avoiding sugary drinks; and limiting consumption of energy-dense foods (particularly processed foods high in added sugar, low in fiber, or high in fat [58]). Additional studies that came after this report support these same conclusions [60,61].…”
Section: Nutritionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the organizations' combined documentFood, Nutrition, Physical Activity and the Prevention of Cancer: A Global Perspective Expert Report-, the main recommendations call for consuming a greater variety of vegetables, fruits, whole grains, and legumes; aiming for meals that consist of two thirds (or more) vegetables, fruits, whole grains, or beans and one third (or less) animal protein; avoiding sugary drinks; and limiting consumption of energy-dense foods (particularly processed foods high in added sugar, low in fiber, or high in fat [58]). Additional studies that came after this report support these same conclusions [60,61].…”
Section: Nutritionsupporting
confidence: 68%
“…The AICR adds that certain foods may be beneficial in cancer care in preventing recurrence including: beans, berries, cruciferous vegetables, flaxseed, garlic, green tea, tomatoes, and others [59,61,[64][65][66]. The AICR emphasizes that no single food or food component by itself can protect against cancer, but the combination of foods in a predominantly plantbased diet may offer protection.…”
Section: Nutritionmentioning
confidence: 99%
“…We have shown that SF is highly effective in blocking ABP-induced DNA damage in human bladder cells in vitro and in mouse bladder tissue in vivo. These findings not only provide further evidence of the chemopreventive activity of SF against bladder cancer but also offer a mechanistic insight into the epidemiological reports that consumption of broccoli is inversely associated with bladder cancer risk and bladder cancer mortality in humans (13,14,38), since SF is considered the key chemopreventive ingredient in broccoli. Although the SF doses used in the animal study (10-40 lmol/kg body weight) are probably .10 times higher than the amount that is typically consumed by a human ($1000 lmol SF per kg fresh broccoli) (39), the animals were exposed to far greater level of ABP (50 mg/kg) than humans normally are because ABP is present at low nanogram levels in the smoke of each cigarette.…”
Section: Nrf2 Is Essential For Sf To Inhibit Abp-dna Adduct Formationmentioning
confidence: 56%
“…Tang et al [112] found that high intake of brassicaceous vegetables modifies bladder cancer survival. They analysed questionnaire data from the Roswell Park Cancer Institute Tumour Registry alongside patient medical records, to examine potential associations between the intake of brassicaceous vegetables (raw versus cooked) and the survival among bladder cancer patients.…”
Section: Proving Efficacy Of Broccoli In Retarding Cancer Progressionmentioning
confidence: 99%